Base of tongue squamous cell carcinoma with infiltrative bone marrow carcinomatosis after definitive chemoradiation: A case report. Issue 7 (15th March 2016) - Christopherson, Kaitlin; Reisman, David N.; Fredenburg, Kristianna; DeJesus, Reordan; Mendenhall, William M.
Abstract: Background: Oropharyngeal squamous cell carcinoma (SCC) is known for its propensity for aggressive local progression and regional lymphatic spread. Distant metastases are relatively uncommon and the likelihood of hematogenous dissemination is primarily related to the extent and location of cervical lymph node metastases. Common sites of distant metastasis include the liver and lung. Methods: We report an unusual case of base of tongue SCC with infiltrative bone marrow carcinomatosis presenting months after definitive chemoradiation despite locoregional control. Results: Our patient exhibited an unusual pattern of distant dissemination after definitive chemoradiation had resulted in locoregional control. Conclusion: Patients who present with bone marrow failure after definitive treatment with apparent disease control should be monitored for bone marrow infiltration by the tumor and, if such infiltration is present, should be evaluated for palliative chemotherapy. Unfortunately, the prognosis for such patients is poor. © 2016 Wiley Periodicals, Inc. Head Neck 38: E2449–E2453, 2016